2001
DOI: 10.1590/s0100-84042001000300003
|View full text |Cite
|
Sign up to set email alerts
|

Pollination ecology of Tabebuia aurea (Manso) Benth. & Hook. and T. ochracea (Cham.) Standl. (Bignoniaceae) in Central Brazil cerrado vegetation

Abstract: -(Pollination ecology of Tabebuia aurea (Manso) Benth. & Hook. and T. ochracea (Cham.) Standl. in Central Brazil cerrado vegetation). The pollination ecology and breeding systems of Tabebuia aurea (Manso) Benth. & Hook., and T. ochracea (Cham.) Standl. were investigated in an area of cerrado vegetation in the Federal District of Brazil. These species occur sympatrically, flower massively and synchronously for a month, during the dry season (July to September). Both have diurnal anthesis, with similar floral st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
22

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 35 publications
(35 reference statements)
1
37
0
22
Order By: Relevance
“…The five individuals studied for the breeding system were strictly self-sterile, which refutes our hypothesis that neopolyploidy can breakdown the LSI, independent of sporophytic apomixis occurrence. Although the small amount of nectar available could force pollinators to visit a greater number of flowers, self-sterility, combined with high rates of geitonogamy, favored by the large number of flowers displayed, can explain the reduced reproductive efficacy observed in our study, as has been reported for other congeneric species (Barros 2001, Bittencourt & Semir 2005. In addition, although we observed floral visitors for a period of only 6 h, the low number of visits by effective pollinators could also explain the low reproductive efficacy.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The five individuals studied for the breeding system were strictly self-sterile, which refutes our hypothesis that neopolyploidy can breakdown the LSI, independent of sporophytic apomixis occurrence. Although the small amount of nectar available could force pollinators to visit a greater number of flowers, self-sterility, combined with high rates of geitonogamy, favored by the large number of flowers displayed, can explain the reduced reproductive efficacy observed in our study, as has been reported for other congeneric species (Barros 2001, Bittencourt & Semir 2005. In addition, although we observed floral visitors for a period of only 6 h, the low number of visits by effective pollinators could also explain the low reproductive efficacy.…”
Section: Discussionsupporting
confidence: 55%
“…In Handroanthus serratifolius, anthesis is irregular in terms of the timing of corolla opening and lasts for approximately three days, as in other Handroanthus species (Vitali & Machado 1995;Barros 2001). However, the flowers are fully receptive only on the first day, as observed for the self-sterile species H. ochraceus (Barros 2001). The maintenance of less receptive flowers could also increase the attraction of bees from greater distances (Ishii et al 2008).…”
Section: Discussionmentioning
confidence: 92%
“…A presença de apenas um embrião adventício em algumas sementes pode ser justificada pela não fecundação da oosfera ou pela degeneração do embrião zigótico, devido à competição com o adventício. Uma outra possibilidade seria a ocorrência de autoincompatibilidade de ação tardia, já verificada em populações de T. ochracea (Gibbs & Bianchi 1993, Barros 2001, que permitiria a germinação do tubo polínico e impediria a formação de embriões sexuados, mas não do endosperma necessário para o desenvolvimento dos embriões apomíticos. Tais casos são desfavoráveis sob o ponto de vista evolutivo, uma vez que diminuem a variabilidade genética da espécie.…”
Section: Discussionunclassified
“…& Hook. ; além de compensarem os danos feitos por Trigona spinipes (Fabricius, 1793) aos frutos de T. ochracea (Barros 2001). Essa mesma autora verificou a ausência de apomixia em T. ochracea através de polinizações controladas, entretanto ela considerou como apomixia o desenvolvimento de embriões sem a ocorrência de polinização, um estímulo necessário ao desenvolvimento dos embriões adventícios nas populações em estudo.…”
Section: Discussionunclassified
See 1 more Smart Citation